Saccharomycopsis schoenii and Saccharomycopsis crataegensis effect on B1 and G1 aflatoxins production by Aspergillus parasiticus in peanut (Arachis hypogaea L.) - Prado, Guilherme (2008)
Aflatoxins are a group of secondary metabolites produced mainly by Aspergillus flavus, A. parasiticus and A. nomius. The effect of S. schoenii and S. crataegensis in the production of aflatoxin B1 and G1 in peanuts, cultivar IAC Caiapó was investigated. Previously autoclaved and in nature peanuts samples were inoculated with A. parasiticus (1.6 x 106 spores.mL-1) and yeast cultures (1.6 x 108 cells.mL-1), followed by incubation at 25oC for seven days. Two experiments were carried out: for the first one, the filamentous fungi and the yeast suspensions were inoculated simultaneously. In the second experiment, the filamentous fungi were inoculated 3 h after yeasts inoculation. Aflatoxin quantification was performed by thin layer chromatography. The production of B1 and G1 aflatoxin was reduced in the presence of the yeasts. The percentage of reduction in aflatoxin concentration was higher when the filamentous fungus was inoculated3 h after adding yeast suspension. The reduction of B1 aflatoxin concentration came to 89.3% and 82.6%, in the presence of S. schoenii and S. crataegensis, respectively. The G1 aflatoxin levels were reduced in91.2% in the presence of S. schoenii and 93.2% in the presence of S. crataegensis.